2016
DOI: 10.3390/ijfs4010004
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of the European Non-Life Insurance: CEO Power, Macroeconomic, and Market Characteristics Impact

Abstract: Abstract:A numbers of studies focusing on the determinant of the insurance market efficiency have increased in the last decade. In fact, many factors, like the CEO's power, can influence the efficiency in the insurance firm. The purpose of this research is to analyze the relationship between efficiency, measured by the cost function using the stochastic frontier approach (SFA) methodologies, and the market structure, as well as the macroeconomic variables. In addition, it focuses on identifying the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There is a number of studies that emphasize the need to analyse and monitor the demand for insurance products and its variability over time with respect to use of the marketing tools and campaigns [5,6]. Many businesses find that their working capital is fluctuating over time due to fluctuations in demand and seasonality of demand [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a number of studies that emphasize the need to analyse and monitor the demand for insurance products and its variability over time with respect to use of the marketing tools and campaigns [5,6]. Many businesses find that their working capital is fluctuating over time due to fluctuations in demand and seasonality of demand [7].…”
Section: Introductionmentioning
confidence: 99%
“…This difference is possibly attributed to the larger sample we use, since Zhang and Bartles (1998) showed that the larger the sample, the lower is the average efficiency scores under the ceteris paribus hypothesis, and/or the different time period of each study. Bahloul and Bouri (2016) also estimated cost efficiency for a balanced panel of 125 non-life insurance companies of seven major European countries for the period 2002-2008 using SFA methodology. Adopting the Flexible Fourier form for the cost function, they found that their sample had an average cost efficiency of 0.692 for the whole sample period.…”
Section: Empirical Results For the European Property-liability Insurance Sectormentioning
confidence: 99%
“…The procedures that are followed for the estimation of the stochastic cost frontiers in the presence of panel data are identical with those developed for the estimation of stochastic production frontier models. We assume that we have a panel of I producers for T time periods 9 . We also assume that cost efficiency is time-invariant and that the deterministic kernel of the stochastic cost frontier takes the single-output Cobb-Douglas form.…”
Section: Panel Data Models For Estimating Cost Efficiencymentioning
confidence: 99%
See 2 more Smart Citations